Handbook of research on teaching and learning in K-20 education - Wang, Victor C. X. (Advances in educational marketing, administration, and leadership (AEMAL) book series)
"This reference provides well-rounded research in providing teaching and learning theories that can be applied to both adults and children while acknowledging the difference between both"--